2017
DOI: 10.5489/cuaj.4472
|View full text |Cite
|
Sign up to set email alerts
|

Does cranberry have a role in catheter-associated urinary tract infections?

Abstract: Introduction: Catheter-associated urinary tract infections (CA-UTIs) are a prevalent and costly condition, with very few therapeutic options. We sought to evaluate the efficacy of an oral cranberry supplement on catheter-associated urinary tracts infections over a six-month period. Methods: Subjects with long-term indwelling catheters and recurrent symptomatic CA-UTIs were enrolled to take a once-daily cranberry supplement -an oral cranberry supplement with 36 mg of the active ingredient proanthocyanidin (PACs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The antiadhesion effect of cranberry is attributed to its high molecular mass constituents (Sobota 1984;Ofek et al 1996;Burger et al 2000;Weiss et al 2002). Likewise, many recent clinical studies proved the efficiency of cranberry in prevention of UTIs (Maki et al 2016;Fu et al 2017;Nabavi et al 2017;Thomas et al 2017). This study did not report bactericidal activity towards planktonic ( inflating the balloon, were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiadhesion effect of cranberry is attributed to its high molecular mass constituents (Sobota 1984;Ofek et al 1996;Burger et al 2000;Weiss et al 2002). Likewise, many recent clinical studies proved the efficiency of cranberry in prevention of UTIs (Maki et al 2016;Fu et al 2017;Nabavi et al 2017;Thomas et al 2017). This study did not report bactericidal activity towards planktonic ( inflating the balloon, were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the preventive effect of cranberry products against UTI have been evaluated in several patient populations and many of these studies suggest that cranberry may reduce the incidence of bacteriuria and UTI (Vasileiou et al ). Recently, it was demonstrated that daily oral intake of cranberry may be beneficial to reduce the number of symptomatic catheter‐associated UTIs in all patients (Thomas et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, small scale clinical studies of concentrated proanthocyanins, extracted from cranberry, have indicated daily consumption in capsules could reduce the incidence of symptomatic CAUTI (Thomas et al . ). Although blockage specifically was not examined in this study, and it is not clear if this will also be effective in controlling encrustation.…”
Section: Approaches To Control Crystalline Biofilm Formation and Cathmentioning
confidence: 97%